PTU-180 Role Of Body Composition And Metabolic Dysfunction In Barrett's Oesophagus And Progression To Cancer. (9th June 2014) - DiCaro, S; Cheung, WH; Keane, M; Haidry, R; Lovat, L; Fini, L; Batterham, R; Banks, M
Abstract : Introduction: Oesophageal adenocarcinoma (OAC) arises within Barrett's oesophagus (BE). Obesity is associated with metabolic syndrome (MS) and cancer progression. Body composition has a direct impact in obesity-related diseases. Normal weight individuals with increased fat mass are considered metabolically obese. Methods: To evaluate the prevalence of obesity, altered body composition and metabolic indexes in patients (pts) with and without BE; and association with cancer progression in BE. In sequential pts undergoing gastroscopy, MS, waist/hip ratio (WHR) and body fat% (BF by bioimpedance analysis) were obtained. In BE pts, histological findings were correlated with metabolic data. Pts were classified according to Body Mass Index (BMI), abdominal obesity (AO by WHR) and in females, Normal Weight Obese (NWO). Identified risk factors significantly associated with BE at univariate analysis were subsequently entered into a multivariate logistic regression analysis. Results: 250 cases and 230 controls (F/M: 193/287) were enrolled. Age (cut off: 57 years) and male gender (M/F 193/57; OR 5.01, p < 0.0001) were identified risk factors for BE. AO (76 vs 51%; OR 3.13; p < 0.001), increased BF% (30.7 vs 17.6%; p = 0.001), higher BMI (overweight: 39.6 vs 30%; OR 2.09; p = 0.0008; obese: 32 vs 22%; OR 2.3; p = 0.004) and MS (33.2 vs 20%; OR 1.95; p = 0.0017) were significantly associated with BE. A positive trend, possibly related to the small number of female cases, was demonstrated for NWO (28.1 vs 19.1%; OR 1.06; p = 0.1). More cases were affected by hypertension (37.4 vs 21.3%; OR 2.4; p < 0.001) and hyperlipidaemia (72.8 vs 53.9%; OR 2.28; p < 0001) but not diabetes. When adjusted by gender, age and race into a multivariate analysis, independent risk factors for BE were BF% (OR 1.90; p = 0.01) and AO (OR 1.67; p = 0.03). Metaplasia and dysplasia were present in 57.2 and 42.8%. AO was the only metabolic parameter independently correlated with high grade dysplasia (38 vs 21%; OR 2.44; p = 0.001). Conclusion: Abdominal obesity, and body fat mass are strong risk factors for BE. A positive trend association was demonstrated in NWO. Furthermore, abdominal adiposity plays a role in progression to OAC. BE might therefore be considered in the metabolic syndrome spectrum and as such, in this group screening interventions may be considered. Disclosure of Interest: None Declared.